A Look Into the Power of fNIRS Signals by Using the Welch Power Spectral Estimate for Deception Detection - Zhang, Jiang; Zhang, Jingyue; Ren, Houhua; Liu, Qihong; Du, Zhengcong; Wu, Lan; Sai, Liyang; Yuan, Zhen; Mo, Site; Lin, Xiaohong (Frontiers in Human Neuroscience, 2021)
Neuroimaging technologies have improved our understanding of deception and also exhibit their potential in revealing the origins of its neural mechanism. In this study, a quantitative power analysis method that uses the Welch power spectrum estimation of functional near-infrared spectroscopy (fNIRS) signals, was proposed to examine the brain activation difference between the spontaneous deceptive behavior and controlled behavior. The power value produced by the model was applied to quantify the activity energy of brain regions, which can serve as a neuromarker for deception detection. Interestingly, the power analysis results generated from the Welch spectrum estimation method demonstrated that the spontaneous deceptive behavior elicited significantly higher power than that from the controlled behavior in the prefrontal cortex (PFC). Meanwhile, the power findings also showed significant difference between the spontaneous deceptive behavior and controlled behavior, indicating that the reward system was only involved in the deception. The proposed power analysis method for processing fNIRS data provides us an additional insight to understand the cognitive mechanism of deception.